2018
DOI: 10.2478/ajis-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of Flood Risks and Disaster Preparedness in Lagos Megacity, Nigeria

Abstract: Flood risks are considered as one of the most devastating natural disasters. Presently, flooding occurs in all the ecological zones in Nigeria which has been linked to global warming. In Lagos Megacity, the incidence of flooding is now a reoccurring decimal which is only an indication of the failure of the existing mechanism for flood risk reduction. Knowledge of public perception of flood risk is considered a crucial element for a proactive preparedness for flood risk reduction. This study is aimed at gaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…This positive relationship is consistent with the findings of other studies (Miceli et al 2008 ; Paton et al 2008 ; Ruin et al 2007 ). Thus, there is need for more perception and awareness creation on the damages of flood risk among the residents in the study area (Onwuemele 2018 ). Burningham et al highlight the importance of engaging with local perspectives on risk and making residents be a part of ‘awareness-raising’ processes (Burningham et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…This positive relationship is consistent with the findings of other studies (Miceli et al 2008 ; Paton et al 2008 ; Ruin et al 2007 ). Thus, there is need for more perception and awareness creation on the damages of flood risk among the residents in the study area (Onwuemele 2018 ). Burningham et al highlight the importance of engaging with local perspectives on risk and making residents be a part of ‘awareness-raising’ processes (Burningham et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian tersebut mengatakan bahwa tidak ada korelasi antara pengalaman bencana sebelumnya dengan kesiapsiagaan perawat dalam menghadapi bencana banjir dengan p value 0,256. Namun, sebaliknya penelitian ini tidak sejalan dengan Onwuemele A (2018) 8 yang melakukan penelitian di Lagos Megacity, Nigeria. Onwuemele mengatakan bahwa seseorang yang mempunyai pengalaman mengalami banjir di masa lalu, maka akan lebih peduli terhadap risiko banjir yang mungkin terjadi dibanding dengan responden yang belum pernah mengalami bencana banjir di masa lalu 8 .…”
Section: Hasilunclassified
“…Namun, sebaliknya penelitian ini tidak sejalan dengan Onwuemele A (2018) 8 yang melakukan penelitian di Lagos Megacity, Nigeria. Onwuemele mengatakan bahwa seseorang yang mempunyai pengalaman mengalami banjir di masa lalu, maka akan lebih peduli terhadap risiko banjir yang mungkin terjadi dibanding dengan responden yang belum pernah mengalami bencana banjir di masa lalu 8 . Novita (2015) juga menyatakan hal yang sama yaitu, ada hubungan antara pengalaman sebelumnya dengan kesiapsiagaan masyarakat menghadapi bencana banjir dengan p value 0,014 9 .…”
Section: Hasilunclassified
See 1 more Smart Citation
“…On the aspect of awareness to flood risk due to sea level rise, [24] showed that it was higher among residents who had experienced flooding previously than those without any experience. However, building regional citizens' knowledge base about current and future flood risks and the benefits and consequences of options to reduce flood risk was quite inevitable [25].…”
Section: Brief Review Of Previous Researchmentioning
confidence: 99%